Fiber optic based continuous wave functional near infrared spectroscopy system - Özkerim, Barış. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2008., 2008)
In the last decade, functional near-infrared spectroscopy (fNIRS) has been introduced as a new neuroimaging modality with which to conduct functional brain studies that require data collection from vision center or motor cortex. The main problem to get data from these regions is the presence of hair on the scalp. Furthermore, animal imaging requires miniaturized source and detectors to be placed on animal surface but there are no such components manufactured. Whereas, the use of fiber-coupled sources and detectors have allowed the investigation of cortical hemodynamics that lie underneath places covered with hair and also allowed the examination of the hemodynamic changes on the animal muscles. The study is involved with driving and modulating two near infrared lasers as well as coupling the resulting coherent and collimated lights to the optical fibers via the optical converters. In addition, fiber optic cables with large core diameters are used to transmit the scattered light from the tissue to the photodetectors. The main goal of the study is to develop a portable and robust fNIRS system for the detection of cortical hemodynamic changes occurring during motor and visual tasks as well as for the study of animal hemodynamics. The ability and effectiveness of the system is tested by several experiments based on the phantom, human and animal studies. Although the system can successfully operate up to one and a half centimeter source detector distance which is enough to examine the hemodynamic changes in the muscle and to work on the animal surface, it is not sufficient to examine the changes during the brain activity. This is mainly due to low signal to noise ratio (SNR) that can be increased with more powerful and fiber-pigtailed lasers.|Keywords: Near infrared spectroscopy, Optical imaging, Laser drivers.
Keywords: Near infrared spectroscopy.; Imaging systems in medicine.